Estimation of Electric Vehicle Battery Health Status Considering Topographic Conditions - Chavez-Orostica, H; Fuentes-Parra, C; Riquelme-Vera, E; Quiroz-Moreno, J; Gonzalez-Pincheira, L (Institute of Electrical and Electronics Engineers Inc., 2023)
The increasing use of electric vehicles entails significant challenges related to battery maintenance and life extension. Within this context, various effective methods have been proposed to evaluate battery health. However, current methods have not considered geographical variables in predicting battery health. In this paper, a fuzzy logic-based method for estimating battery degradation is proposed. This model takes into account the topography of the area where the vehicle is used. To validate its effectiveness, simulations are carried out in Santiago (Chile) and Valparaï¿½ï¿½so (Chile), revealing that both the maximum charge and the internal resistance of the battery, influenced by terrain inclination, are critical factors in their degradation. These simulations demonstrate that the proposed model is useful for estimating battery health. © 2023 IEEE.